Seagrass-macroalgal interactions in a changing ocean - Richard, Maddi; Quijón, Pedro A. (Frontiers in Climate, 2023)
The number of reports highlighting the services provided by seagrass beds continues to be matched by those reporting on local seagrass declines across the world coastlines. Among the many factors driving the fate of seagrass beds, this Mini Review focuses on the interactions between seagrasses and algae, more specifically, macroalgae. Seagrasses are known to respond to sudden increases in cooccurring macroalgae, and the ongoing warming of ocean waters suggests that these interactions are most likely to grow in frequency and possibly in intensity in the decades ahead. What remains unclear is the nature (positive, neutral, negative) and the local outcome of those interactions. We examined the published evidence on explicit seagrass-algal interactions and found that in most cases these interactions have been negative, with seagrass species most often found at a competitive disadvantage with regards to macroalgae. Rising ocean temperatures are likely to add to this imbalance as at least some studies already suggest that the negative effects of macroalgae and warming are either additive or synergistic. The further examination of these effects will help predict likely future scenarios and aid in the prioritization of conservations efforts.